Communities in Colonial Mexico Under Spanish Colonial Rule - Smith, Vannessa (The Toro Historical Review, 2020)
Prior to World War II and the subsequent social rights movements, historical scholarship on colonial Mexico typically focused on primary sources left behind by Iberians, thus revealing primarily Iberian perspectives. By the 1950’s, however, the approach to covering colonial Mexican history changed with the scholarship of Charles Gibson, who integrated Nahuatl cabildo records into his research on Tlaxcala. Nevertheless, in his subsequent book The Aztecs under Spanish Rule Gibson went back to predominantly Spanish sources and thus an Iberian lens to his research. It was not until the 1970s and 80s that U.S. scholars, under the leadership of James Lockhart, developed a methodology called the New Philology, which focuses on native-language driven research on colonial Mexican history. The New Philology has become an important method of research in the examination of native communities and the ways in which they changed and adapted to Spanish rule, while at the same time holding on to some of their own social and cultural practices and traditions. This historiography focuses on continuities and changes in indigenous communities, in particular the evolution of socio-political indigenous structures and socio-economic relationships under Spanish rule, in three regions of Mexico: Central Mexico, Yucatan, and Oaxaca.